The Queen v Louis Riel - Riel, Louis, 1844-1885; Morton, Desmond (Social history of Canada ;, 1974)
The transcript of Louis Riel's trial has never been readily accessible to the general reader interested in the 1885 Rebellion and related events. This work will promote knowledge of the facts, and illustrate a social phenomenon of nineteenth-century Canada. In that age litigation was a prime public spectacle, and the trial of Louis Riel in 1885 was followed intently across the country. The crowded, stuffy courtroom in Regina was the stage for the most dramatic and perhaps the most important state trial in Canadian history. In his introduction, Desmond Morton has sought to banish many of the myths which surround both Riel and the trial, doing justice to Madconald and the government as well as to the prisoner of Regina. In the process, he has restated the issues of the trial in the terms understood by his contemporaries.